A theoretical framework to study the impact of integrity practises on teachers quality in rural schools - Latifah Mohd Zain @ Matjin; Soon Singh Bikar Singh; Zulfhikar Rabe; Ibnis Shaid Abdul Rajun; Amran Manining (Malaysian Journal of Social Sciences and Humanities (MJSSH), 2024)
The changes of globalisation in the flow of education challenge teachers to wisely adapt changes to improve the delivery of existing education. Innovation in education is in line with the rapid pace of the Industrial Revolution 4.0, which plays an important role in producing creative and innovative students. Teachers serve as catalysts for change for students to develop analytical, critical, and creative thinking to become skilled and competitive individuals. However, the growing issue of integrity also requires awareness among teachers of the importance of practising integrity to improve self-quality. Integrity issues in the field of education tarnish the good name of education itself and have resulted in the credibility of teachers being often disputed. The National Integrity Plan was launched in 2004 to address the problem of leakage among civil servants, including teachers. This situation results in the quality of teachers being tarnished and requires support from professional organisations in order to mobilise energy in an integrated and holistic manner to improve the quality of teachers and school performance. Based on the literature review, this article presents the Theory of Personal Psychology and Integrity Strengthening Model to evaluate the effect of integrity practises on the quality of teachers and further strengthen the level of teacher professionalism in rural areas. This theoretical framework study contributes to the management of integrity practises in schools and the Ministry of Education Malaysia, especially in improving the quality and professionalism of teaching.